(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2022)
The risk of disseminated Histoplasmosis increases among immunocompromised HIV infected patients. It can clinically present with skin manifestation. We report a forty years HIV infected male with severe immunodeficiency clinically presenting as a disseminated Histoplasmosis with dermatological manifestation and diagnosis.